The Effect of Current Ratio and Debt to Equity Ratio on Deviding Growth - Yusni Nuryani; Denok Sunarsi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to study the Effect of Current Ratio and Debt to Equity Ratio on Dividend Change at PT. Gajah Mas. The method used is an explanatory research analysis technique using statistical analysis with regression testing, testing, determination and hypothesis testing. . Debt to Equity Ratio has a significant effect on the estimated dividend of 34.2%, the hypothesis test obtained significance of 0.045 <0.05. Current Ratio and Debt To Equity Ratio significant to Dividend conversion of 47.8%, the hypothesis test obtained significance of 0.014 <0.05.